The Effect of Work Discipline, Work Engagement, Work Attitude and Commitment on Employee Performance in the Pamong Praja Police Unit, Labuhan Batu Regency - Nurul Azmi Tambak; Yuniman Zebua; Siti Lam'ah Nasution (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to analyze the effect of work discipline, work involvement, work attitude and commitment to employee performance in the Civil Service Police Unit, Labuhan Batu Regency. This type of research is quantitative, the place of this research is the Civil Service Police Unit on Jalan WR. Supratman No. 46, Labuhanbatu. Data collection techniques used in the study were observation, documentation and questionnaires using a Likert scale. In this study, the population was the Pamong Praja Rantau Prapat police unit as many as 233 people. The sample was taken using the Slovin formula, which was determined or the significance level was 0.05, so the sample size in this study was 147 people multiple linear regression equation as follows: Y=1.459+0.170X1+0.402X2 +0.152X3+0.159X4. Table 6 explains that the B value in work discipline (B1) is 0.170. The value of work involvement (B2) is 0.402. The value of work attitude (B3) is 0.152. The commitment value (B4) is 0.159, and the constant value (a) is 1.459. The description of the multiple linear regression equation shows that the variables of work discipline (X1), work involvement (X2), and commitment (X4) have a positive direction coefficient on employee performance. The value of Fcount is 50.710> Ftable 2.43 with a significance value of 0.000 <0.05. From these results, it can be concluded that work discipline (X1), work involvement (X2), work attitude (X3), and commitment (X4) simultaneously have a positive and significant effect on employee performance (Y). The value of R Square from the analysis of the coefficient of determination of 0.588 means that work productivity can be explained by the variables of work discipline (X1), work involvement (X2), work attitude (X3), and commitment (X4) of 58.8%, while the remaining 41, 2% can be explained by other variables not examined in this study.